Measurements of meteorological parameter effects on photovoltaic energy production - (:unkn) unknown (North Atlantic University Union, 2015)
Photovoltaic systems (PV) use solar cells convert the sun's rays into electricity by exciting electrons in the cells using the photons of light from the sun. These conversion efficiency mainly related sun's rays and solar cells. The conditions which are effects sun's rays and solar cells firmly related with energy outputs of the PV systems. The energy yield is strongly associated with the weather because the electrical energy is produced directly from the solar energy. Most of the PV energy prediction models based on the meteorological parameters such as solar radiation, ambient temperature, relative humidity, wind speed, clearness index and sunshine duration. These meteorological parameters are associated with the geographical conditions where the PV systems installed. In this study, identical two photovoltaic panel systems are established in Istanbul and Kirklareli at Marmara region. Photovoltaic panel outputs and surface temperatures, solar irradiance values and meteorological parameters are measured and analyzed to find out regional differences. © 2015, North Atlantic University Union. All rights reserved.
Keywords: Energy production; Meteorological parameters; Photovoltaic system; Regional differences; Solar radiation; Surface temperature